Finite-difference time-domain analysis of the vibration characteristics of a beam-plate structure using a dimension-reduced model. (May 2015) - Asakura, T.; Ishizuka, T.; Miyajima, T.; Toyoda, M.
Abstract: In order to accurately predict the vibration characteristics of structure-borne sound transmission in buildings, wave-based numerical methods are effective from the viewpoint of the modeling accuracy of the physical mechanism and the detailed geometries of the simulated field. However, because of the performance of current PCs, the prediction of real-scale problems remains difficult. In order to address such problems, we herein propose a vibration simulation method for a beam-plate structure using a dimension-reduced modeling method. The target structure is modeled as a composite structure consisting of two-dimensional plate elements and one-dimensional beam elements, which are coupled based on the implicit finite-difference approximation scheme. By applying such a low-dimensional element, a faster simulation that requires less memory, as compared with a three-dimensional discretization scheme, is made available. Good agreement between the measured and simulated results for the vibration characteristics of acrylic beam-plate models indicates the validity of the proposed method.